2008
DOI: 10.4314/gjass.v7i1.2358
|View full text |Cite
|
Sign up to set email alerts
|

Farmers\' Characteristics And Adoption Of Recommended Practices Under The Fadama Project Scheme In Edo State, Nigeria

Abstract: The study focused on farmers under the fadama project scheme in Edo State, Nigeria with emphasis on the relationship between farmers' characteristics and adoption of recommended technologies. Analyses of data obtained from a random sample of 80 respondents reveals that fadama farming was dominated by females (62.5%), most of whom were married (77.5%), above 32 years (77.5%), and poorly educated. Gender, educational and household characteristics of respondents were significant determinants of respondents' adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Education of the respondents had significant positive relationship with the adoption of BARI recommended potato varieties indicating that more education of the respondents leads to a tendency towards more adoption. Similar relationship was also obtained by Hoque et al, (2010), Omoregbee and Okoedo-Okojie, 2008;Saka et al, 2005;Salasya et al, 2007;Amin andIslam, 2009, Akter (2007), Aurangozeb (2002), and Sardar (2002). Knowledge of the farmers on improved potato production technologies also showed significant positive relationship with adoption of BARI recommended potato varieties.…”
Section: Relationship Between Socio-economic Characteristics Of the Rsupporting
confidence: 82%
“…Education of the respondents had significant positive relationship with the adoption of BARI recommended potato varieties indicating that more education of the respondents leads to a tendency towards more adoption. Similar relationship was also obtained by Hoque et al, (2010), Omoregbee and Okoedo-Okojie, 2008;Saka et al, 2005;Salasya et al, 2007;Amin andIslam, 2009, Akter (2007), Aurangozeb (2002), and Sardar (2002). Knowledge of the farmers on improved potato production technologies also showed significant positive relationship with adoption of BARI recommended potato varieties.…”
Section: Relationship Between Socio-economic Characteristics Of the Rsupporting
confidence: 82%
“…This supports the findings of Omorogbee et al in a study of farmers in Nigeria. 25 , 26 They tended to have a poor educational background, many years of farming experience and the majority were married, with many household members to feed. 26–28 These circumstances seem likely to have increased farmers' desire to adopt innovations to enhance production, and produce surplus crops to sell for profit.…”
Section: Discussionmentioning
confidence: 99%
“…Thus they indicated that presently they prefer to patronise licensed private rice processors who buy their rice harvest to process and subsequently market to the public. This is supported by Adeleye , [18] Ibitoye ,[8] Onje , [27] West [26] which stated that dishonesty among cooperative leaders, fear of being cheated and mistrust among cooperative members were factors hindering the involvement of agro based cooperatives in the marketing of agricultural products in Nigeria. ▪ Absence of a felt need to run a business oriented venture among cooperative members.…”
Section: Resultsmentioning
confidence: 87%
“…This is in line with studies by Agbonlahor et al [24] Agbo [25] which noted that most cooperative members in Nigeria indicated that their major reason for joining cooperatives was to access credit facilities and other farm-inputs thus affirming that access to funds remains the major economic benefit farmers expect from agro based cooperatives in Nigeria. Studies by Omotesho et al [3] Omoregbee and Okojie [26] also observed that over the years, there has been an increase in the formation of agro based cooperatives evident in the increasing number of registered agro based cooperatives in the various states in Nigeria. However they observed that most of these cooperatives were formed with the sole aim of obtaining funds with most of them disappearing on obtaining the expected funds.…”
Section: Review Of Agricultural Cooperatives In Nigeriamentioning
confidence: 94%